Current advances in the treatment of giant cell arteritis: the role of biologics. (February 2019) - Low, Candice; Conway, Richard
Giant cell arteritis (GCA) is the most common form of systemic vasculitis. It is a potentially severe disease with 25% of patients suffering vision loss or stroke. Our treatment paradigm is based on glucocorticoids. Glucocorticoids are required in high doses for prolonged periods and subsequently are associated with a significant amount of treatment-related morbidity. Alternative treatment options are urgently needed to minimize these glucocorticoid adverse events. Many other agents, such as methotrexate and tumour necrosis factor alpha inhibitors have been used in GCA, with limited or no evidence of benefit. Our emerging understanding of the pathogenic processes involved in GCA has led to an increased interest in the use of biologic agents to treat the disease. Two randomized controlled trials have recently reported dramatic effects of the use of the interleukin-6 targeted biologic tocilizumab in GCA, with significant increases in remission rates and decreases in glucocorticoid burden. While encouraging, longer-term and additional outcomes are awaited to clarify the exact positioning of tocilizumab in the treatment approach. Emerging data for other biologic agents, particularly abatacept and ustekinumab, are also encouraging but less well advanced. We are at the dawn of a new era in GCA treatment, but uncertainties and opportunities abound.